DIROFILARIASIS IN DOGS IN VORONEZH AND VORONEZH REGION - T. A. Zolotykh; N. S. Bespalova (Российский паразитологический журнал)
The results for the dissemination of heartworm in dogs from Voronezh and the Voronezh region are obtained. Materials and methods. Dirofilariasis was detected in 52 cases (12,3%) of the investigated 424 blood samples. Results and discussion. EI is different in various social dog groups: 24,1% - among the homeless (of 29), 24,6% - security (of 65) and 8,8% of 330 dogs kept in housing conditions and private homes. Dirofilariasis was registered in all age groups of 1 to 14,5 years, but the highest invasion rate (42,2%) was observed in dogs 1 to 5 years of age. The subcutaneous dirofilariasis (Dirofilaria repens) is twice as often as the cardiovascular dirofilariasis (D. Immitis).